The impact of genomic architecture and diversity on infectious diseases - Chow, Vincent; Sakharkar, Meena (Henry Stewart Talks, 2019)
Genome related paradoxes, Sequencing the human genome, Homologs of human proteins, The genetic basis of human complexity, Human genetics vs. mouse genetics, Exons and introns in the human and mouse genomes, Conclusions about eukaryotic genomes, Viral genomes and reverse vaccinology, Pathogenesis of viral infections, Infectomics and virogenomics of different viruses (SARS, HPV, Dengue & E71), Diagnostic virology, Gene knockdown strategies & siRNA